Modelling the student academic mobility e-service: an approach of sensemaking and the work system framework / Umi Nadia Abdul Basitt - Abdul Basitt, Umi Nadia (2021)
The higher education market has grown notably due to the globalization impact that influences the higher education providers to create internationalization activities such as student academic mobility program. Demand of academic mobility from the students worldwide is expected to grow positively in the future. This research is conducted to investigate the strategic approach on higher education management to address operational efficiency of student academic mobility services using Malaysian student academic mobility as a context of case study. Student academic mobility is a complex situation involving multi-stakeholder from domestic and foreign counterparts. The case study investigates student academic mobility phenomena that influence operational efficiency of student academic mobility services before proceeding with a thorough and holistic description of the student academic mobility e-service framework as a strategic approach. Preliminary study was conducted to reckon the relevancy of this research area which then unveil that the student academic mobility services are afflicted with variety of issues centered mainly on inefficient of work process. This research is investigated from two main studies which reflected the perspectives of supply and demand sides of student academic mobility services. The first study looks into the supply side involves interviews conducted with the student academic mobility providers from strategic, tactical and operational management levels followed by document reviews of the student academic mobility. The second study looks into the demand side involves interviews conducted with the mobility students to delve into issues of student academic mobility services. The interviews were conducted based on semi-structured questions constructed from the work system framework. A qualitative analysis by integrating socio-technical system approach that is work system method with knowledge management method that is sensemaking is adapted in each study to describe phenomena of student academic mobility. A detailed analysis using work system method and value chain analysis were conducted to produce a detailed view of student academic mobility e-service framework from prescriptive view. Student academic mobility e-service framework verification was conducted to better understand the research findings and to obtain verification from the experts to prove that it is viable. These research outcomes contribute to the body of knowledge in information systems analysis and design based on the use of work system method to analyse and design the work system of student academic mobility. Other novelty is the methodological contribution in using work system method integrated with data/frame theory of sensemaking. This innovation augments the existing methods by establishing greater capability to address operational efficiency of student academic mobility.